Coastal thermal springs in a foreland setting: The Santa Cesarea Terme system (Italy). (November 2016) - Santaloia, F.; Zuffianò, L.E.; Palladino, G.; Limoni, P.P.; Liotta, D.; Minissale, A.; Brogi, A.; Polemio, M.
Highlights: Offshore sea-water recharges coastal, sulhpurous, thermal springs. A deep hydrothermal-convection system, controlled by fault zones, is discovered. The integration of methodologies represents a key-factor for geothermal exploration. Abstract: Carbonate aquifers in foreland tectonic settings can host important thermal springs although located in areas commonly not characterized by regional high heat flow values. In these cases, when thermal springs are located close or along the coastlines the subaerial and/or submarine thermal springs constitute the outflow of marine groundwater, flowing through localized fractures and karsitic rock-volumes. This is the case of springs occurring along the south-easternmost portion of the Apulia region (Southern Italy) where few sulphurous and warm waters (22–33 °C) outflow in partially submerged caves located along the shoreline, thus supplying the historical spas of Santa Cesarea Terme. Here, with the aim to define the origin of the thermal fluids and their deep path, we carried out the geo-structural survey of the area and detailed hydrogeological and geochemical analyses of the thermal spring fluids. In particular, the isotopes δ 18 O, δD, 13 C in DIC, 34 Ssulphate, 34 Ssulphide, 3 He/ 4 He ratio and 13 C in CO2 were used to define the origin of the thermal water and the recharge mechanism of the geothermal system while the isotopes 3 H and 14 C were determined for estimating the age of the thermal waters, resulting in older than roughly twenty thousands years BP. The results indicate that the thermal springs are fed by marine water, having reached Santa Cesarea Terme through a localized fracture network. This affects the evaporitic and carbonatic rocks that characterize the substratum of the Adriatic Sea in the offshore.